Effects of electronic cigarettes and hookah (waterpipe) use on home air quality. Issue 1 (21st May 2021) - Shearston, Jenni A; Eazor, James; Lee, Lily; Vilcassim, M J Ruzmyn; Reed, Taylor A; Ort, Deborah; Weitzman, Michael; Gordon, Terry
Abstract : Introduction: A major site of secondhand smoke exposure for children and adults is the home. Few studies have evaluated the impact of e-cigarette or hookah use on home air quality, despite evidence finding toxic chemicals in secondhand e-cigarette aerosols and hookah smoke. We assessed the effect of e-cigarette and hookah use on home air quality and compared it with air quality in homes where cigarettes were smoked and where no smoking or e-cigarette use occurred. Methods: Non-smoking homes and homes where e-cigarettes, hookah or cigarettes were used were recruited in the New York City area (n=57) from 2015 to 2019. Particulate matter with diameter less than 2.5 µm (PM2.5 ), black carbon and carbon monoxide (CO) were measured during a smoking or vaping session, both in a 'primary' smoking room and in an adjacent 'secondary' room where no smoking or vaping occurred. Log transformed data were compared with postanalysis of variance Tukey simultaneous tests. Results: Use of hookah significantly increased PM2.5 levels compared with non-smoking homes, in both the primary and secondary rooms, while use of e-cigarettes increased PM2.5 levels only in primary rooms. Additionally, in-home use of hookah resulted in greater CO concentrations than the use of cigarettes in primary rooms. Conclusions: Use of e-cigarettes or hookah increases air pollution in homes. For hookah, increases in PM2.5 penetrated even into rooms adjacent to where smoking occurs. Extending smoke-free rules inside homes to include e-cigarette and hookah products is needed to protect household members and visitors from passive exposure to harmful aerosols and gases.